Sigajang Laleng Lipa: Kearifan lokal dalam keragaman Budaya Masyarakat Bugis - Femas, Anis (Maliki Interdisciplinary Journal, 2024)
This article was created by the author to discuss Local wisdom is a cultural heritage that has been passed down from generation to generation, it reflects the identity and uniqueness of a society. One example of local wisdom that is rich in cultural values is the Bugis diversity of Si Gajang Laleng Lipa. Bugis is an ethnic group in Indonesia that has a diverse culture that includes aspects such as customs, language, arts, and other unique traditions. Sigajang laleng lipa is an integral part of Bugis life. This concept encompasses a deep understanding of harmony and balance between humans, nature and the supernatural. This diversity of Bugis sigajang laleng lipa is not only reflected in traditional rituals and ceremonies, but also in traditional art, music, dance, and distinctive traditional clothing. This study aims to document and further understand the local wisdom of Bugis Sigajang Laleng lipa diversity, and identify its important role in enriching the cultural heritage of the nation. Through a greater understanding of the uniqueness of Bugis culture and its contribution to Indonesia's overall cultural richness.